1983
DOI: 10.1002/j.1552-4604.1983.tb01800.x
|View full text |Cite
|
Sign up to set email alerts
|

Food Increases the Bioavailability of Isotretinoin

Abstract: Twenty healthy male subjects received 80 mg (2 X 40 mg SEG capsules) oral isotretinoin separated by two-week washout periods in an open randomized crossover design. Isotretinoin was administered during a complete fast, 1 hour after a standard breakfast, with a standard breakfast, or 1 hour before a standard breakfast. Blood samples were obtained at specific times over a 72-hour period. Isotretinoin blood concentrations were determined by a specific HPLC method. The relative bioavailability (AUC) of isotretinoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0
4

Year Published

1987
1987
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(48 citation statements)
references
References 7 publications
1
43
0
4
Order By: Relevance
“…No attempt was made to control food intake around the time of administration. A previous study has reported higher plasma concentrations when 13-cisRA was administered within 1 h before or after a standard meal, compared with the fasted state (Colburn et al, 1983). Application of the data presented here to guide dosing of 13-cisRA would also need to be adapted to reflect differences in the administration of 13-cisRA in different countries, for example punching a hole in the capsule so that it can be chewed before swallowing.…”
Section: Discussionmentioning
confidence: 93%
“…No attempt was made to control food intake around the time of administration. A previous study has reported higher plasma concentrations when 13-cisRA was administered within 1 h before or after a standard meal, compared with the fasted state (Colburn et al, 1983). Application of the data presented here to guide dosing of 13-cisRA would also need to be adapted to reflect differences in the administration of 13-cisRA in different countries, for example punching a hole in the capsule so that it can be chewed before swallowing.…”
Section: Discussionmentioning
confidence: 93%
“…The subset of patients who needed at least one additional course of OI usually completed this within 2 to 3 years, of their initial course [1, 4, 12••, 13-17••, [18][19][20][21][22][23][24][25]. Given the same duration of OI therapy which was usually 16 to 20 weeks, a consistent trend for recurrence of AV has been observed in several studies, with a lower daily dose (0.1 -0.2 mg/kg/day) associated with a higher recurrence rate and often an earlier onset of recurrent AV as compared to higher daily doses (0.5-mg/kg/day; 1 mg/ kg/day) [12••, 13-17••, [18][19][20][21][22][23][24][25]. The culmination of data analysis supports that a course of OI achieves a total dose of 120 -50 mg/kg to reduce the potential for recurrence of AV (Table 1) [17••, 18-22].…”
Section: Outcomes From Data Analyses On Need For Retreatment After Ormentioning
confidence: 99%
“…Human pharmacokinetic data could be described by bi-or triexponential equations (Khoo et al, 1982), but a recycling model fit the plasma data best. The presence of food in the gut and the type of pharmaceutical preparation (Colburn et al, 1983b;Shelley et al, 1982) can affect the absorption of the drug. Peak circulating plasma concentrations and bioavailablility were greater when the drug was administered following a meal than when the gut was empty (Colburn et al, 1983b).…”
Section: Pharmacokineticsmentioning
confidence: 99%
“…The presence of food in the gut and the type of pharmaceutical preparation (Colburn et al, 1983b;Shelley et al, 1982) can affect the absorption of the drug. Peak circulating plasma concentrations and bioavailablility were greater when the drug was administered following a meal than when the gut was empty (Colburn et al, 1983b). The elimination half-lives in man ranges from 4 (Kerr et al, 1982) to 13 to 14 (Colburn et al, 1983a) to 25 h (Goodman et al, 1982; Neither the parent nor its metabolite, all-.tmru.-RA, is eliminated in the urine; they are primarily eliminated in the feces (Khoo et al, 1982).…”
Section: Pharmacokineticsmentioning
confidence: 99%